Discovery of an inflated hot Jupiter around a slightly evolved star TOI-1789. Issue 3 (23rd October 2021) - Khandelwal, Akanksha; Chaturvedi, Priyanka; Chakraborty, Abhijit; Sharma, Rishikesh; Guenther, Eike W; Persson, Carina M; Fridlund, Malcolm; Hatzes, Artie P; Prasad, Neelam J S S V; Esposito, Massimiliano; Chamarthi, Sireesha; Nayak, Ashirbad; et al.
ABSTRACT: We report here the discovery of a hot Jupiter at an orbital period of 3.208664 ± 0.000015 d around TOI-1789 (TYC 1962-00303-1, TESS mag = 9.1) based on the TESS photometry, ground-based photometry, and high-precision radial velocity (RV) observations. The high-precision RV observations were obtained from the high-resolution spectrographs, PARAS at Physical Research Laboratory (PRL), India, and TCES at Thüringer Landessternwarte Tautenburg (TLS), Germany, and the ground-based transit observations were obtained using the 0.43-m telescope at PRL with the Bessel- R filter. The host star is a slightly evolved (log g * = 3.943^+0.023_-0.043 ), late F-type ( T eff = 5991 ± 55 K), metal-rich star ([Fe/H] = 0.373^+0.071_-0.086 dex) with a radius of R_* = 2.168^+0.036_-0.034 R ⊙ located at a distance of 223.53^+0.91_-0.90 pc. The simultaneous fitting of the multiple light curves and the RV data of TOI-1789 reveals that TOI-1789 b has a mass of M_P = 0.70 ± 0.16 M_J, a radius of R_P = 1.44^+0.24_-0.14 R_J, and a bulk density of ρ P = 0.28^+0.14_-0.12 g cm −3 with an orbital separation of a = 0.04882^+0.00063_-0.0016 au. This puts TOI-1789 b in the category of inflated hot Jupiters. It is one of the few nearby evolved stars with a close-in planet. The detection of such systems will contribute to our understanding of mechanisms responsible for inflation in hot Jupiters and also provide an opportunity to understand the evolution of planets around stars leaving the main-sequence branch.